Contagion of populist extremism - Daiki Kishishita; Atsushi Yamagishi (Osaka University, Institute of Social and Economic Research (ISER), 2020)
To explore the propagation of undesirable policies in a form of populist extremism, we construct a social learning model featuring agency problems. Politicians in different countries sequentially implement a policy. Voters learn the incumbent politician's type and the desirable policy by observing foreign policies on top of the domestic policy. We show that populist extremism is contagious across countries through the dynamic interaction between the changing public opinion and implemented policies. This structure yields interesting long-run dynamics. First, a single moderate policy could be always enough to stop the domino effect. Second, the persistence of the domino effect depends on the correlation of the desirable policy across countries. In particular, while extremism eventually ends under the perfect correlation, it may become impossible to escape from extremism under the imperfect correlation. These results reveal a new negative aspect of decentralized policymaking.
Keywords: D72; D83; H73; 330; Political agency; Yardstick competition; Populism; Observational learning; Signaling